2021
DOI: 10.1080/15389588.2021.1904138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of a digital voice assistant to maintain driver alertness in partially automated vehicles

Abstract: Objective: Vehicle automation shifts the driver's role from active operator to passive observer at the potential cost of degrading their alertness. This study investigated the role of an in-vehicle voice-based assistant (VA; conversing about traffic/road environment) to counter the disengaging and fatiguing effects of automation. Method: Twenty-four participants undertook two drives-with and without VA in a partially automated vehicle. Participants were subsequently categorized into high and low participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A significant difference was found on the KSS, indicating that playing Tetris led to a lower fatigue level than no NDRA. This was confirmed by the analysis of PERCLOS and the expert rating by Wiegand et al [36]. Moreover, takeover performance was assessed by takeover time, time-to-collision, and maximum lateral and longitudinal acceleration, though no significant differences were found between Tetris and no NDRA.…”
Section: Types Of Countermeasuresmentioning
confidence: 58%
See 3 more Smart Citations
“…A significant difference was found on the KSS, indicating that playing Tetris led to a lower fatigue level than no NDRA. This was confirmed by the analysis of PERCLOS and the expert rating by Wiegand et al [36]. Moreover, takeover performance was assessed by takeover time, time-to-collision, and maximum lateral and longitudinal acceleration, though no significant differences were found between Tetris and no NDRA.…”
Section: Types Of Countermeasuresmentioning
confidence: 58%
“…The authors showed lower subjective fatigue ratings on the Karolinska Sleepiness Scale (KSS) created by Åkerstedt and Gillberg [37] and higher pupil diameter, indicating higher alertness in the drive with a speech-based assistant. Thus, fatigue symptoms were reduced with assistants, but cognitive workload was higher when driving with a speech-based assistant [36]. Moreover, no drivers nodded off when driving with a speech-based assistant, while six nodded off when driving without one.…”
Section: Types Of Countermeasuresmentioning
confidence: 94%
See 2 more Smart Citations
“…The PVT is a simple sustained attention task that measures objective alertness by assessing the reaction speed of the brain to external sensory stimuli. 41 To eliminate the intervention effects of the acoustic environment on fatigue, 42 a 5-minute visual version of PVT was employed with a red dot randomly appearing at the centre of the computer screen (Interstimulus Interval (ISI): 2000–10 000 ms). The participants were asked to keep their index finger on the space key and press it as soon as they see a red dot (Figure 4(a)).…”
Section: Methodsmentioning
confidence: 99%